Recent advances in ordered meso/macroporous metal oxides for heterogeneous catalysis: a review. Issue 19 (21st April 2017) - Wang, Yuan; Arandiyan, Hamidreza; Scott, Jason; Bagheri, Ali; Dai, Hongxing; Amal, Rose
Abstract : The present review article highlights the preparation, characterization, properties, and recent developments in porous metal oxide catalysts for heterogeneous catalysis. Abstract : Ordered meso/macroporous metal oxides have gained increasing attention in heterogeneous catalysis arising from their large surface areas and pore volumes, elevated catalytic activity and good thermal stability. Compared to nonporous metal oxides, their most prominent feature is the ability to interact with molecules not only at their exterior surface but also within the large interior surface of the material. The past decade has witnessed substantial advances in the synthesis of new porous metal oxides with ordered structures for use in a wide range of applications. By recalling some of the classical fundamentals of porous materials, this review examines the recent developments in ordered meso- and macro-porous metal oxide catalysts for heterogeneous catalysis. Additionally, we outline the current challenges in the field of nanoparticle-based catalysis, including the role played by the morphology (size, shape, and porosity) of ordered meso/macroporous metal oxides, and provide a perspective on the need for further advances in porous materials so that their contribution to heterogeneous catalysis can continue to expand.